Evaluation of Radiation Doses in Radiotherapy Using Cone-Beam Computed Tomography - Kazim, Hussein Hadi; Shamkhi, Hussein Maher; Abbas, Fatima Kazim; Star, Raghad Khaled; Mohammed, Zahraa Jafar (American Journal of Botany and Bioengineering, 2025)
Dose distributions in the Image Gently and Image Wisely campaigns were estimated by using Monte Carlo methods to calculate doses to organs in radiation treatment planning phantom models. The phantoms, representing the average individual of four age groups, were standardized by using reference body and organ masses defined within International Commission on Radiological Protection Publications for an adult male. They were implemented into the EGSnrc radiation transport code and coupled to a model of a Siemens Artiste linear accelerator equipped with both an OBI system and an MV cone beam CT system. Open fields were irradiated in anterior-posterior and lateral setups to calculate organ doses and effective doses resulting from irradiation of a head and a chest phantom. In the latter setup, the head phantom, representing a child, was also exposed by using an adult protocol to simulate overshooting of the primary beam, in particular in cone-beam CT exposures. Organs within and outside of the primary x-ray beams were evaluated as a function of beam energy and patient size, and overall effective dose was calculated. The effective doses in CBCT scans were also compared with those in kVCT scans which replace the CBCT scans in the treatment planning process. In order for treatment procedures to be optimized, the doses delivered by imaging exposures should be taken into account. Though the essential characteristics of CBCT systems and CT simulators are the same, the CT dosimetry methods based on the CT dose index that have been widely used are not feasible for CBCT imaging devices. The most important distinction is the large variability in patient exposure for CBCT systems because different scanners use different imaging protocols, each composed of a variety of parameters that determine the final dose delivered to the patient. Currently, the CTDI method has been modified for CBCT systems and the results have been published in a report. Given the potential for significant differences in dose delivery between different modes of imaging, it’s essential that doses resulting from a given protocol and machine can be accurately estimated.